2002
DOI: 10.1007/s00213-002-1118-y
|View full text |Cite
|
Sign up to set email alerts
|

Is withdrawal-induced anxiety in alcoholism based on β-endorphin deficiency?

Abstract: Our results give first evidence that lowered beta E during alcohol withdrawal may contribute to anxiety as a common disturbance during this state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…Our findings solidify a connection between cocaine-seeking behavior and the endogenous opioids and corroborate the findings of many other groups (Olive et al, 2001;Kiefer et al, 2002;Marinelli et al, 2003Marinelli et al, , 2004Roth-Deri et al, 2003Shaw and al'Absi, 2008;Seo et al, 2009;Nguyen et al, 2012;Dikshtein et al, 2013;Zhou et al, 2013). b-endorphin is known to play an important role in addictions.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings solidify a connection between cocaine-seeking behavior and the endogenous opioids and corroborate the findings of many other groups (Olive et al, 2001;Kiefer et al, 2002;Marinelli et al, 2003Marinelli et al, , 2004Roth-Deri et al, 2003Shaw and al'Absi, 2008;Seo et al, 2009;Nguyen et al, 2012;Dikshtein et al, 2013;Zhou et al, 2013). b-endorphin is known to play an important role in addictions.…”
Section: Discussionsupporting
confidence: 91%
“…Investigations of recovering alcoholics have shown that levels of plasma β-endorphin are inversely correlated with self-rated measures of anxiety during the withdrawal period (Kiefer et al, 2002). Augmented negative reinforcement following alcohol consumption for subjects with low β-endorphin is likely because of its role in inhibiting CRH secretion.…”
Section: β-Endorphin and Chronic Alcohol Usementioning
confidence: 99%
“…High levels of cortisol act as negative feedback for HPA axis stress response, (Buckingham, 1986) implicating β-endorphin in both behavioral allostasis and endocrine allostasis. Thus, it is likely that an alcohol-induced reduction of increased basal anxiety levels is a strong negative reinforcing factor in the maintenance of chronic alcohol dependence (Goldowitz et al, 2006;Kiefer et al, 2002).…”
Section: β-Endorphin and Chronic Alcohol Usementioning
confidence: 99%
“…The endogenous opioid system has also been implicated in the modulation of alcohol-induced behaviors and alcohol addiction (de Waele and Gianoulakis, 1993;Kiefer et al, 2002;Oswald and Wand, 2004;Patel and Pohorecky, 1989). In fact, the opioid receptor antagonist naloxone is already in clinical use for relapse prevention in abstinent alcoholics.…”
Section: Stress-induced Ethanol Drinking In Cb1 −/− Pomc and Penk mentioning
confidence: 99%